Perfusion -Weighted Magnetic Resonance Imaging Techniques and Protocols in the Evaluation of Cerebral Blood Flow, Blood Volume, and Vascular Permeability of Brain Neoplasms - Safa Musadaq Abd-ALRahman; Haider Qasim Hamood (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective : To identify the efficiency of perfusion, weighted magnetic resonance imaging techniques andprotocols in, evaluation of cerebral blood, flow, blood volume, & vascular, permeability of a tumor in thebrain in correlation with viability of brain neoplastic tissues.Material and Methods : One hundred and fifteen patients with histologically proven brain tumors wereexamined by 1.5 Tesla PHILIPS MR System. For four months, patients who were referred in an MRIassessment were included in this review. Conventional MRIs protocol, (axial T2WI (TSE), Axial T1WI(FSE), axial T2WI FALIR, axial T1WI post contrast). PW-MRI protocol axial Fast Echo –Echo PlannerImage (FE-EPI) Neuro-T2* Perfusion Dynamic Contrast Enhancement agent (DCE-MRI), (Gadolinium(Gd)contrast Magnevist).Results and discussion: Magnetic Resonance Imaging in (10) patients (8.70%) revealed feature consistentwith brain tumors (control cases), the brain has been evaluated by routine study or conventional (protocolC). (105) patients (91.3%) underwent examination with PW-MRI (FE-EPI) Neuro-T2* Perfusion (DCEMRI)( protocol P). (18) patients (15.65%) with the anaplastic astrocytoma WHO grade (III), (17) patients(14.78%) with metastatic brain tumors, (15) patients (13.04%) with non-recurrence of post-operative braintumors, (11) patients (9.57%) with high grade glioma, (10) patients (8.70%) with craniopharyngioma, (9)patients (7.83%) with glioblastoma multiform WHO grade IV, (9) patients (7.83%) with low grade glioma,(8) patients (6.96 %) with meningioma, the agemistocytic astrocytoma WHO grade(II) was the lowestdiagnosed brain tumor (2.61%).